Climate responsive lessons from an architectural and ethnographic study of Hijazi traditional dwellings in Jeddah, Saudi Arabia - Basunbul, Anwar Islem; Braham, William W. (Frontiers in Built Environment, 2023)
This study investigated the thermal environment in a traditional Hijazi building, the Baeshen House in Jeddah, Saudi Arabia, a city on the Red Sea. This dwelling, which was built in 1856, was designed based on the accumulated local knowledge and experience of the region's conditions. Such buildings were constructed to provide thermal comfort without air conditioning to occupants in the hot humid climate of a coastal area. During the time period of December 2021 to August 2022, on-site monitoring was performed in winter and summer to record and analyze on-field measurements and the effectiveness of thermal comfort strategies. Two different ventilation strategies—i.e. full-day and night-time—were examined. The results showed the thermal mass of the vernacular architecture played an essential role in regulating the indoor air temperature from the extreme outdoor conditions. Moreover, night-time ventilation practices accounted for significant temperature reductions indoors and a more comfortable living environment. It was observed that construction materials, namely Al-Mangabi stones, played a substantial role in Hijazi architecture in mitigating the impact of severely high summer temperatures, as did specific traditional occupant strategies. The study established that natural cooling ventilation strategies are effective for maintaining thermal comfort and are valuable features of vernacular architecture with a substantial application for modern architectural design.